Proporsionalitas Perjanjian Penerbit Dan Penyelenggara Securities Crowdfunding - Adelia Kusuma Wardhani (Faculty of Law Universitas Islam Indonesia, 2022)
The agreement between the issuer and the organizer of the crowdfunding securities can be made in the form of a notarial deed. However, the clauses to be included in such agreement have been regulated through Regulation of Financial Services Authority (POJK) No. 57/POJK.04/2020 on Crowdfunding Services Through Information Technology-Based Securities Offerings. The regulated clause does not describe a balance for both parties. The formulation of the problem in this study is whether the principle of proportionality is required in the agreement between the issuer and the organizer of crowdfunding securities and what the role of the notary should be in formulating the agreement of the issuer and organizer of crowdfunding securities. This is a normative legal research conducted with a statutory and a conceptual approaches. The results of the research and discussion conclude that the Principle of Proportionality in the agreement of issuers and organizers of crowdfunding securities needs to be used to provide legal protection for investors. In addition, the role of the notary is to provide legal counseling to publishers and administrators regarding the agreements that will be made. Even though the clause that has been regulated by the Financial Services Authority cannot be violated, the notary continues to provide legal counseling regarding the legal consequences that will be faced by the parties to the agreement. This is a form of preventive legal protection by a notary for the parties to anticipate the legal consequences that will occur in the futureKey Word: Proportionality, Issuer, Organizer and Crowfunding Securities AbstrakPerjanjian antara penerbit dan penyelenggara securities crowdfunding dapat dibuat dalam bentuk akta Notaris. Namun, klausula yang dicantumkan di dalamnya telah diatur melalui POJK No. 57/POJK.04/2020 tentang Layanan Urun Dana Melalui Penawaran Efek Berbasis Teknologi Informasi. Klausula yang diatur tersebut tidak menggambarkan adanya keseimbangan bagi kedua belah pihaknya. Rumusan masalah dalam penelitian ini yaitu: apakah diperlukan asas proporsionalitas dalam perjanjian antara penerbit dan penyelenggara securities crowdfunding, dan bagaimana peran notaris yang seharusnya dalam pembuatan perjanjian penerbit dan penyelenggara securities crowdfunding. Penelitian ini merupakan penelitian hukum normatif yang dilakukan dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian dan pembahasan menyimpulkan bahwa Asas Proporsionalitas dalam perjanjian penerbit dan penyelenggara securities crowdfunding perlu digunakan untuk memberikan perlindungan hukum bagi pemodal. Selain itu, Notaris berperan untuk memberikan penyuluhan hukum kepada penerbit dan penyelenggara terhadap perjanjian yang akan dibuatnya. Walaupun klausula yang sudah diatur oleh Otoritas Jasa Keuangan tidak dapat disimpangi, notaris tetap memberikan penyuluhan hukum mengenai akibat hukum yang akan dihadapi para pihak dengan perjanjian tersebut. Hal ini menjadi salah satu bentuk perlindungan hukum preventif oleh notaris, agar para pihak dapat mengantisipasi akibat hukum yang akan terjadi di kemudian hari.Kata-kata Kunci:Proporsionalitas, Penerbit, Penyelenggara dan Securities Crowfunding